Fatigue reliability evaluation of Q460 welded joints using fracture fatigue entropy method. (15th April 2021) - Wei, Wei; Du, Liang; yang, Guang; Zhang, Yuntong; Sun, Yang; Yang, Xinhua
Highlights: The infrared thermography data are captured to establish the proposed method. The fatigue limit is well estimated based on the entropy production rate. The P-S-N curves with different survival probability rate are well predicted. This method enables a rapid S-N curve prediction of Q460 welded joints. Abstract: In this paper, the fracture fatigue entropy (FFE) was used to evaluate the fatigue reliability of Q460 welded joints during high-cycle fatigue. The Q460 butt welded joint fatigue tests were conducted under different loads. Meanwhile, the real-time temperature measurement, monitored by an infrared thermal scanner, was completed. The fatigue limit can be well estimated according to the cumulative damage entropy production rate in Phase II, and compared with the fatigue limit prediction value by the traditional staircase method, a good consistency is achieved. Furthermore, the P-S-N curves of 5%, 50%, and 95% survival probability rate are well predicted, which is consistent with the experimental data. Therefore, based on this, the accurate fatigue reliability evaluation based on the proposed method has been achieved.